HUBUNGAN FAKTOR SOSIO DEMOGRAFI DAN PELAYANAN KB DENGAN KEIKUTSERTAAN KB DI WILAYAH KERJA PUSKESMAS BROMO TAHUN 2018 - HELENA FRANSYSCA (LP2MTBM MAKARIOZ, 2021)
This study aims to find out the socio-demographic factors and kb services with kb participation. This research is descriptivecorrelation by using cross sectional method. The population in this study is all fertile age couples (PUS) in the Working Areaof Puskesmas Bromo with sample techniques used is purposive sampling with a total of 83 people. The primary data in thisstudy was obtained from questionnaires and secondary data obtained from the Village Head Office about the number offertile age couples (PUS). The analysis techniques used are univariate analysis and bivariate analysis using Chi-Squarestatistical test. The results of the study obtained no relationship between age and kb participation with (p value 0.512), thereis a relationship between education and kb participation with (p value 0.001), there is a relationship between the number ofchildren with kb participation with (p value 0.000), there is a relationship between family income and kb participation with (pvalue 0.010), there is a relationship between kb services and kb participation with (p value 0.003). It is expected that healthworkers who have an important role in providing information to the community in the form of counseling to increaseknowledge and motivation of the community to participate in kb, for couples of childbearing age can determine the number ofchildren by birth control, if it is more than 35 years old is expected not to get pregnant again.